Mass‐Forming Variants in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: Diagnostic Complexities in Granulomatous Disease. A Case Report - Benedetta Fazzi; Elena Treppo; Simone Longhino; Maria Pillon; Luca Quartuccio (ACR Open Rheumatology)
A middle‐aged woman presented with a granulomatous breast lesion in 2018. By 2021, antibiotic‐resistant pneumonia led to the discovery of granulomatous inflammation in the lung and thyroid. Initially misdiagnosed as Erdheim–Chester disease (ECD), she was treated with interferon without success. Histopathology later ruled out ECD, suggesting an unspecified granulomatous disease, with granulomatosis with polyangiitis (GPA) initially excluded due to negative antineutrophil cytoplasmic antibodies (ANCAs) and foamy histiocytes. In 2023, repeated lung biopsy and PR3‐ANCA positivity led to a revised diagnosis of mass‐forming GPA. Rituximab therapy resulted in remission. This case highlights the diagnostic complexity of GPA with atypical histopathological features.